Tower of the Sun, Golden Gate International Exposition, San Francisco (H.S. Crocker Co., Inc.)
Tower of the Sun as seen from Court of the Moon at the 1939 Golden Gate International Exposition on Treasure Island in San Francisco Bay. Right, the Homes and Gardens Building, showing elaborate detail in sculptures and bas reliefs.